2008
DOI: 10.1111/j.1751-9004.2008.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Seven Pillars of Defense Mechanism Theory

Abstract: Defense mechanisms are cognitive processes that function to protect the individual from excessive anxiety or other negative emotions. They also protect the person from loss of self‐esteem and, in the extreme, the loss of self‐integration. Although past critics questioned the existence of defense mechanisms, recent research has supported seven basic tenets regarding defenses. These include: (1) defenses function outside of awareness; (2) there is a chronology of defense development; (3) defenses are present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 66 publications
4
67
0
4
Order By: Relevance
“…Such processes influence the type of the emotion experienced, the time at which it occurs and how it is perceived and expressed by the subject; and they are implicated in personality, emotional, cognitive, and social development (Gross, 2002). Cramer (2008;2012) defined defenses as mental processes, also present in normal personality, that alter the perception of a disturbing external event or a disruptive inner state with the aim to protect the individual from excessive anxiety or other negative emotions arising from the perception of these stimuli. Although defense mechanisms have been primarily investigated in the contest of clinical research, recently their role in self-regulation, adjustment, and adaptation has been emphasized (Diehl, Chui, Hay, Lumley, Grühn, & Labouvie-Vief, 2014).…”
Section: Emotion Regulation and Defense Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such processes influence the type of the emotion experienced, the time at which it occurs and how it is perceived and expressed by the subject; and they are implicated in personality, emotional, cognitive, and social development (Gross, 2002). Cramer (2008;2012) defined defenses as mental processes, also present in normal personality, that alter the perception of a disturbing external event or a disruptive inner state with the aim to protect the individual from excessive anxiety or other negative emotions arising from the perception of these stimuli. Although defense mechanisms have been primarily investigated in the contest of clinical research, recently their role in self-regulation, adjustment, and adaptation has been emphasized (Diehl, Chui, Hay, Lumley, Grühn, & Labouvie-Vief, 2014).…”
Section: Emotion Regulation and Defense Mechanismsmentioning
confidence: 99%
“…Secondly, they both are involved in the normative development (Cramer, 1991) and play an important role in mental health: the two constructs have been included in the definition of psychological well being (e.g. : Gratz & Roemer, 2004;Cramer 2008). …”
Section: Differences and Similarities In Emotion Regulation And Defenmentioning
confidence: 99%
“…It was found that men use internalizing defenses and projection more than females, and women use externalizing defenses, denial, and reaction formation more than males (Cramer, 2005, 2009) 34,19 . In addition, the current study showed that, the mean score of neurotic mechanisms was higher in females than males.…”
Section: Discussionmentioning
confidence: 99%
“…In more advanced theoretical discussions, defensive mechanisms and coping methods are, however, differentiated. It is mainly believed that coping is an adaptation process, which enables an individual to adapt to goals, whereas defensive mechanisms are connected with an imperative to reduce distress and distort reality (Cramer, 2009;Haan, 1965;Kramer, 2010). In other words, coping is proactive, while defensive mechanisms are triggered as a response to impulse activation, which would lead to a sense of intra-mental threat and fear.…”
Section: Defensive Activitytheoretical Introductionmentioning
confidence: 99%
“…Current research on conceptualizations of defences proves, however, that a defensive mechanism does not need to become a response to an internal conflict or fear, but also frustration, stress, crisis, unpleasant affect, threatened self-esteem or lack of security (Hentshel, Draguns, Ehlers, & Smith, 2004;Kline, 2004;Draguns, 2004). Defences are aimed at self-protection, and are related to self-theories (the more rigid are the theories, the more likely they are to evoke defences, Dweck & Elliott-Moskwa, 2010), self-esteem and emotion regulation (Cramer, 2009;Kernis, Lakey, & Heppner, 2008). According to Feldman Barret et al (2002, p. 3), defensive mechanisms may be treated as motivated cognitive-behavioural strategies, which protect the self from the expected threat, maintain or increase self-esteem, reduce negative affect and maintain positive representations of parental figures.…”
Section: Defensive Activitytheoretical Introductionmentioning
confidence: 99%